0
$\begingroup$

Is this the proper way?

f = 
  3*((A^3 + B^3) - (A^3 + B^3)^(2/3)*B -(A^3 + B^3)^(1/3)*A^2 + A^2*B) == 
  A^3 + B^3 + (A^3 + B^3) + 3*(A + B + (A^3 + B^3)^(1/3))*(AB + A(A^3 + B^3)^(1/3) + 
  B(A^3 + B^3)^(1/3)) - 3AB(A^3 + B^3)^(1/3)

FindInstance[{f, A > 0, B > 0, C > 0}, {A, B, C}, Integers, 5]
$\endgroup$
4
  • $\begingroup$ a and A are different symbols, as are b and B. Next, AB is interpreted as a single vairbale called AB (and you probably want A*B). Finally your symbol (1/3) should be written out as (1/3) just as you wrote out (2/3). $\endgroup$
    – bill s
    Jan 29, 2019 at 15:38
  • $\begingroup$ @bills thanks done $\endgroup$
    – Dale
    Jan 29, 2019 at 15:40
  • 2
    $\begingroup$ There are still ABs occurring in f. Anyways, replacing AB by A B, Reduce[{f, A > 0, B > 0}, {A, B}, Integers] returns False, telling me that there are no solutions. $\endgroup$ Jan 29, 2019 at 16:09
  • $\begingroup$ You can simplify to f = A^3 - 6 B C^2 - 3 B^2 C + B^3 == 3 A (B^2 + 2 B C + C^2 + 2 A C) && A^3 + B^3 == C^3. $\endgroup$
    – Somos
    Jan 29, 2019 at 20:52

1 Answer 1

1
$\begingroup$

You can simplify to

f = A^3 - 6 B C^2 - 3 B^2 C + B^3 == 3 A (B^2 + 2 B C + C^2 + 2 A C) && A^3 + B^3 == C^3

but there are no positive solutions. Define

f[A_, B_] := With[{c = (A^3 + B^3)^(1/3)}, 
             A^3 - 6 B c^2 - 3 B^2 c + B^3 - 3 A (B^2 + 2 B c + c^2 + 2 A c)];

and Plot3D[ f[x, y], {x, 0, 2}, {y, 0, 2}] makes it obvious that f[x, y] < 0 for all positive values of x and y.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.